Eventful Cities : Cultural management and urban revitalisation - Richards, Greg.; Palmer, Robert (Amsterdam ; London : Butterworth-Heinemann, 2010)
Cities used to compete to be monumental - now they compete to be eventful. This book analyses the process of cultural event development, management and marketing, and links these processes to their wider cultural, social and economic context.
Includes bibliographical references and index.
Keywords: Special events -- Europe -- Management -- Case studies; Urban renewal -- Europe -- Case studies; City promotion -- Europe -- Management -- Case studies; Urban economics; Special events -- Management; Urban renewal; City promotion -- Management; Society